Acceleration Method Eradication of Qur'an Illiteracy in Indonesia - Syukri, Ahmad (Penerbit Goodwood, 2025)
Purpose: This paper addresses efforts to accelerate the eradication of Qur’anic illiteracy in Indonesia. Recent studies (2018–2023) indicate that a significant number of Muslims still experience difficulties in reading the Qur’an, particularly in recognizing and pronouncing Arabic script, although the percentage has shown gradual decline. The study aims to present and evaluate various methods for learning Qur’anic script, ranging from classical to contemporary approaches. Research Methodology: The research employs a qualitative descriptive approach through a library study. Data were collected and analyzed from scholarly works, educational materials, and expert writings that discuss different methods of teaching Qur’an reading skills. Results: The findings reveal several methods designed to accelerate the eradication of Qur’anic illiteracy. Among them, modern methods demonstrate higher levels of practicality, efficiency, and accessibility compared to purely classical approaches, making them more suitable for rapid learning among today’s Muslim communities. Conclusions: Effective eradication of Qur’anic illiteracy requires combining the strengths of both classical and modern teaching methods. Integrating practicality with cultural-religious values ensures broader acceptance and sustainability of literacy programs. Limitations: The study is limited to secondary data from existing literature and does not include field validation or empirical testing of the methods reviewed. Contribution: This paper contributes by offering a comparative overview of Qur’anic literacy methods and highlighting those most relevant for accelerating literacy programs in contemporary Muslim societies.